Insights into the effect of different levels of crude oil on hydrolyzed polyacrylamide biotransformation in aerobic and anoxic biosystems: Bioresource production, enzymatic activity, and microbial function. (December 2019) - Zhao, Lanmei; Cheng, Yuan; Yin, Zichao; Chen, Dafan; Bao, Mutai; Lu, Jinren
Graphical abstract: Highlights: The effect of crude oil on HPAM biotransformation was explored for the first time. The highest PHA yield increased with the increase of crude oil concentration. The highest dehydrogenase activity rose with increasing crude oil concentration. PHA yield, dehydrogenase activity and HPAM removal were closely related. Microbial function related to HPAM biodegradation and PHA synthesis was discussed. Abstract: The differences of crude oil recovery ratio resulted in different levels of crude oil in actual hydrolyzed polyacrylamide (HPAM)-containing wastewater. The effect of crude oil on HPAM biotransformation was explored from bioresource production, enzymatic activity and microbial function. In aerobic biosystems, the highest polyhydroxyalkanoate (PHA) yield (19.6%–40.2%) and dehydrogenase (DH) activity (4.06–8.32 mg·g –1  VSS) occurred in the 48th hour, and increased with crude oil concentration (0–400 mg·L –1 ). In anoxic biosystems, the highest PHA yield (24.5%–50.5%) and DH activity (3.24–6.69 mg·g –1  VSS) occurred in the 72nd hour, and increased with crude oil concentration. The higher substrate removal (38.5%–65.7%) occurred in aerobic biosystems, while the higher PHA accumulation occurred in anoxic biosystems. PHA yield, DH activity and HPAM removal were related. Microbial function related to HPAM biodegradation and PHA synthesis was discussed. The main function of Pseudomonas and Bacillus in aerobic biosystems was to degrade HPAM, and in anoxic biosystems was to synthesize PHA.